Report on fraying resilience among the Ontario Registered Practical Nurse Workforce in long‐term care homes during COVID‐19 - Denise M. Connelly; Nancy Snobelen; Anna Garnett; Nicole Guitar; Cecilia Flores‐Sandoval; Samir Sinha; Jen Calver; Diana Pearson; Tracy Smith‐Carrier (Wiley, 2023)
Abstract Aim Registered Practical Nurses (RPNs) are frontline healthcare providers in Ontario long‐term care (LTC) homes. Throughout COVID‐19, RPNs working in LTC homes experienced prolonged lockdowns, challenging working conditions, and inadequate resource allocation. This study aimed to describe the personal and professional resilience of RPNs working in LTC during the COVID‐19 pandemic. Design An open cross‐sectional online survey containing the Connor-Davidson Resilience Scale, Resilience at Work Scale®, and Resilience at Work Team Scale®. Methods The survey was distributed by the RPN Association of Ontario (WeRPN) to approximately 5000 registered members working in Ontario LTC homes. Results A total of 434 respondents participated in the survey (completion rate = 88.0%). Study respondents scored low on measures of resilience and reported extreme levels of job (54.5%) and personal (37.8%) stress. Resources to support self‐care and work‐life balance, build capacity for team‐based care practice(s) are needed.